The beginner's goodbye : a novel - Tyler, Anne. (New York : Alfred A. Knopf, 2012)
"Explores how a middle-aged man, ripped apart by the death of his wife, is gradually restored by her frequent appearances-- in their house, on the roadway, in the markets ... Only Dorothy's unexpected appearances from the dead help him to live in the moment and to find some peace."--Provided by publisher
Keywords: Middle-aged men -- Fiction; Wives -- Death -- Fiction; Bereavement -- Fiction; Psychological fiction